Use of clays in the treatment of radioactive aqueous waste generated at the CDTN - Hellen Késia Santos de Souza; Maria Judite Afonso Haucz; Carolina Braccini Freire (Brazilian Journal of Radiation Sciences, 2025)
Radioactive waste is generated in various activities carried out by industry, whether focused on agriculture, energy, health, or research development. CNEN defines it as all materials with radionuclides above clearance levels, generated by human action, whose use is inappropriate or not foreseen. Proper management is essential to ensure the population's safety, workers occupationally exposed to radiation, and the environment. The research by institutes that develop nuclear technologies generates solid and liquid radioactive waste. To reduce their volume, solid waste is compacted or immobilized in a cement matrix, and liquid waste is treated in such a way as to concentrate the radionuclides present and separate them from the liquid part to release this liquid part in the environment, according to the acceptance criteria of CNEN standard. There are several ways to treat liquid waste, such as precipitation, sorption, ion exchange, membrane filtration, and evaporation. In this work, the precipitation followed by sorption in commercial clays of some liquid radioactive waste generated through research carried out at the Nuclear Technology Development Center was evaluated to reduce the radionuclides content in the aqueous part and concentrate the radionuclides in the clays used.